2014 IEEE International Conference on Information and Automation (ICIA) 2014
DOI: 10.1109/icinfa.2014.6932702
|View full text |Cite
|
Sign up to set email alerts
|

Design and application of lighting energy consumption monitoring platform based on MVC and entity framework

Abstract: With the development of intelligent lighting technology and green lighting, energy-saving has become an important direction of research and development. A lighting energy consumption monitoring platform has been designed and described in the paper based on Model-View-Controller (MVC) software architecture and Entity framework on .Net platform. The energy consumption of the lighting system before and after the using of energy-saving equipment can be monitored, compared and analyzed, which can provide detailed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Systems developed by using Ado.Net or Entity Framework technologies can also be given as examples of these systems. The Entity Framework technology was used in the system developed by Xie et al [16] in order to store and display data and a significant reduction was observed in energy consumption of the system. Also in the study conducted by Zhongming et al [17], the Entity Framework was used for data management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Systems developed by using Ado.Net or Entity Framework technologies can also be given as examples of these systems. The Entity Framework technology was used in the system developed by Xie et al [16] in order to store and display data and a significant reduction was observed in energy consumption of the system. Also in the study conducted by Zhongming et al [17], the Entity Framework was used for data management.…”
Section: Literature Reviewmentioning
confidence: 99%